Using paleomagnetism to determine the heating effect of lava flows on underlying substrates - Lerner, Geoffrey A. (2023)
The extent to which heat from lava flows passes into underlying and adjacent materials has significant implications for volcanic hazard studies. Here we demonstrate how paleomagnetism can be used as a tool to determine the heating effects of lava flows in the pre-existing substrates over which they flow. Samples from soils taken beneath lava flows from Rangitoto and Puketutu eruptive centres (Auckland Volcanic Field, Aotearoa New Zealand) and a human-made berm beneath the June 27th Lava Flow (2014-2015; K¯ılauea Volcano, Hawaii, USA) were subjected to progressive thermal demagnetization to assess the strength and stability of their remanent magnetizations. The temperature and depth to which these soils display a strong coherent magnetization represents the extent to which they were remagnetized (and therefore heated) by the overlying flow. Results suggest heating to at least 570 ℃ at depths of up to 21 cm below the substrate-flow contact. This information is valuable for constraining and validating heat transfer models, which can be used to assess the lava flows' subterranean thermal hazard. Among many uses, this is vital for emergency management planning for buried infrastructure networks traversing regions that could be exposed to effusive volcanic activity. Further afield, in astrobiology, it might find application in determining the thickness of a substrate layer heated sufficiently by a lava flow to kill living organisms.